2017
DOI: 10.3233/mnm-16119
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value, phytochemicals and antioxidant properties of two wild edible fruits (Eugenia operculata Roxb. and Antidesma bunius L.) from Assam, North-East India

Abstract: The purpose of present study was to investigate the nutritional composition, phytochemical contents and antioxidant capacities of two wild edible fruits viz. Eugenia operculata Roxb. and Antidesma bunius L. from Assam of North-East India. The fruits showed variable amounts of proximate and mineral compositions which are reported herein and discussed. The phytochemical screening of different solvent extracts exhibited the presence of many phytochemicals which are biologically important. The antioxidant activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…Our findings showed that phytochemical compounds were detected from the remaining fraction after removing organic acids and sugars. Interestingly, the fraction of Thai berry extracts had higher content of anthocyanins than previous studies of Prunus domestica [ 32 , 33 ], Antidesma bunius [ 12 , 34 ], Syzygium cumini [ 35 ], and Syzygium nervosum [ 15 , 36 ]. In the current study, the correlations between phytochemical compounds in the extract and the lipid-lowering activity were also found.…”
Section: Discussionmentioning
confidence: 61%
“…Our findings showed that phytochemical compounds were detected from the remaining fraction after removing organic acids and sugars. Interestingly, the fraction of Thai berry extracts had higher content of anthocyanins than previous studies of Prunus domestica [ 32 , 33 ], Antidesma bunius [ 12 , 34 ], Syzygium cumini [ 35 ], and Syzygium nervosum [ 15 , 36 ]. In the current study, the correlations between phytochemical compounds in the extract and the lipid-lowering activity were also found.…”
Section: Discussionmentioning
confidence: 61%
“…It is recommended for the treatments of cough, asthma, dysentery, bloated stomach, stomachache, fever, inflammation, vomiting, anal fistula, and urinary disorders, as documented in the Myanmar traditional medicine [89]. The ethanol extract of T. triquetrum contains triquetrumones A (23), B, and C, (R)-triquetrumone D (24), cyclokievitone, yukovanol, aromadendrin, kaempferol, astragalin, 2-O-methyl-L-chiro-inositol, galactitol, p-hydroxycinnamic acid, ursolic acid, betulinic acid, βsitosterol, daucosterol, stigmasterol, stigmasta-5,22-dien-3-O-β-Dglucopyranoside, saccharose, docosanoic acid [183], triquetrumones E-H [184], tadehaginosin (25), and 3,4-dihydro-4-(4'hydroxyphenyl)-5,7-dihydroxycoumarin [185]. Zhang et al, in extensive investigations of this plant, has revealed the presence of various types of phenylpropanoid glucosides, including tadehaginoside (26), tadehaginoside A (27), and tadehaginoside B-I [186].…”
Section: Stemona Burkilliimentioning
confidence: 99%
“…Antidote, syphilis, insect bites and stings [17] Antioxidant [22][23][24], antidiabetic [25][26][27][28][29], antimicrobial [30], pesticide [31], and cytotoxic activities [32] Anti-inflammatory [57], hepatoprotective [53,58], chemopreventive [53], cytotoxic, antimicrobial, antitubercular, antimycotic [54], and antioxidant activities [56] 7. Ficus heterophylla L.f. Moraceae Leaves, barks Flatulence, asthma and dysentery [17] No report 8.…”
Section: Stemona Burkilliimentioning
confidence: 99%
See 1 more Smart Citation
“…Fig.2Comparative accounts of DPPH • (IC 50 µg/mL) of O. smaragdina, Odontotermes sp., conventional food of plant origin (fruit and vegetables), common edible insects (Values other than those of O. smaragdina and Odontotermes sp., adapted from Zielinska et al[22], Chatsuwan et al[23], Islary et al[24], Tsiba et al[25] and Saiki et al[26] …”
mentioning
confidence: 99%